Sistem Pendukung Keputusan Penentuan Status Gizi Buruk Pada Balita Menggunakan Metode Fuzzy Mamdani - Sari, Dian Permata Sari Permata (STKIP PGRI Sumatera Barat, 2015)
Malnutrition is a condition when a person is declared lack of nutrients, or in other meanhis/her nutrients or nutritional status are below of average standards. As consequent will born unproductive human resources so will impact on all aspects of life. Based on these problems we need a method to determine the nutritional status of babies in order to handle of malnutrition. With the decision support system, it can be easier to monitor the growth and development of babies health and to facilitate decision-making in malnutrition treatment tounder five years old childrens. Fuzzy logic is a problem-solving control system method, which is suitable to implement on a systems and supported by Mamdani method. The data used as input were age, body weight, and body length and conducted a manual search using Mamdani and do Matlab test. If the babies has low age, light of weight, and average body length so the nutritional status is very low. Although the results of the manual calculation and Matlab result is not the same, but still in the same range. As an example,the results obtained using manual search using Mamdani method is 27.7 andthe result of Matlab testis 32.9 both of them have 5.2 difference, but still in the same range with very poor nutritional decisions